Experimental Manipulation of Food Accessibility Affects Conflict Management Behaviour in Ravens. (February 2016) - Sima, Miriam Jennifer; Pika, Simone; Bugnyar, Thomas
Abstract: Conflict management strategies such as reconciliation and bystander affiliation have been described for a variety of species. A common determinant seems to be a 'complex' social life, with individuals relying on affiliate relationships or social bonds. Little is known, however, about the strategic and flexible use of conflict management skills in experimental settings in species other than primates. We here investigated conflict and post‐conflict behaviour of ravens by manipulating the accessibility of food and, thus, the likelihood of aggressive interactions while foraging. Specifically, we presented birds with a certain amount of highly preferred food that varied in the number of pieces (one piece, two pieces or, as a control, small pieces matching the number of participating birds) and observed their agonistic behaviour during feeding and their affiliative behaviour afterwards. The results showed that high levels of conflicts during feeding in the 1‐piece and 2‐piece conditions led to high levels of affiliation after feeding. Depending on the experimental condition, this effect is best explained (a) by the affiliative behaviour of former aggressors (1‐piece condition) and (b) by the affiliation directed to the receivers of aggression after feeding (2‐piece condition). Those dyads that engaged in allo‐preening after feeding also engaged in allo‐preening outside the experimental setting, suggesting that socially bonded individuals provided third‐party affiliation to victims of aggression. Moreover, socially bonded ravens fed close to each other in the experiment when food was clumped, indicating that they actively coordinated their behaviour when there was a high conflict potential. Taken together, these findings support the assumption that ravens use their social bonds to avoid conflicts by choosing with whom to feed, and to buffer effects of conflicts by engaging in third‐party affiliation as post‐conflict behaviour.